Greater Adherence to Cancer Prevention Guidelines Is Associated with Higher Circulating Concentrations of Vitamin D Metabolites in a Cross-Sectional Analysis of Pooled Participants from 2 Chemoprevention Trials. Issue 3 (25th January 2017) - Kohler, Lindsay N; Hibler, Elizabeth A; Harris, Robin B; Oren, Eyal; Roe, Denise J; Jurutka, Peter W; Jacobs, Elizabeth T
Abstract: Background: Several lifestyle factors targeted by the American Cancer Society (ACS) Nutrition and Physical Activity Cancer Prevention Guidelines are also associated with circulating concentrations of vitamin D metabolites. This suggests that greater adherence to the ACS guidelines may be related to better vitamin D status. Objective: We examined the relation between adherence to the ACS guidelines and circulating concentrations of 2 vitamin D metabolites, 25-hydroxycholecalciferol [25(OH)D] and 1α, 25-dihydroxyvitamin D [1, 25(OH)2 D]. Methods: We conducted cross-sectional analyses of pooled participants from the Wheat Bran Fiber ( n = 503) and Ursodeoxycholic Acid ( n = 854) trials. A cumulative adherence score was constructed with the use of baseline data on body size, diet, physical activity, and alcohol consumption. Continuous vitamin D metabolite concentrations and clinically relevant categories were evaluated with the use of multiple linear and logistic regression models, respectively. Results: The most adherent participants were more likely to be older, white, and nonsmokers than were the least adherent. A statistically significant association was observed between guideline adherence and concentrations of circulating 25(OH)D (means ± SEs—high adherence: 32.0 ± 0.8 ng/mL; low adherence: 26.4 ± 0.7 ng/mL; P -trend < 0.001). For 1, 25(OH)2 D concentrations, high adherence was again significantly related to greater metabolite concentrations, with mean ± SE concentrations of 36.3 ± 1.3 pg/mL and 31.9 ± 1.0 pg/mL for high- and low-adherers, respectively ( P -trend = 0.008). Furthermore, the odds of attaining a sufficient 25(OH)D status were 4.37 times higher for those most adherent than for those least adherent (95% CI: 2.47, 7.71 times). Conclusion: These findings demonstrate that greater adherence to the ACS guidelines is associated with higher circulating concentrations of both of 25(OH)D and 1, 25(OH)2 D.